Results of a round-robin exercise on read-across. Issue 5 (3rd May 2016) - Benfenati, E.; Belli, M.; Borges, T.; Casimiro, E.; Cester, J.; Fernandez, A.; Gini, G.; Honma, M.; Kinzl, M.; Knauf, R.; Manganaro, A.; Mombelli, E.; et al.
Abstract: A round-robin exercise was conducted within the CALEIDOS LIFE project. The participants were invited to assess the hazard posed by a substance, applying in silico methods and read-across approaches. The exercise was based on three endpoints: mutagenicity, bioconcentration factor and fish acute toxicity. Nine chemicals were assigned for each endpoint and the participants were invited to complete a specific questionnaire communicating their conclusions. The interesting aspect of this exercise is the justification behind the answers more than the final prediction in itself. Which tools were used? How did the approach selected affect the final answer?